ChemInform Abstract: Highly Enantioselective Catalytic [6 + 3] Cycloadditions of Azomethine Ylides. Issue 8 (1st March 2013) - Potowski, Marco; Bauer, Jonathan O.; Strohmann, Carsten; Antonchick, Andrey P.; Waldmann, Herbert
Abstract The highly regio‐ and enantioselective reaction yields complex annulated piperidines with 8 stereocenters.